Crop residue management and its impacts on soil properties - He, Yuxin (Kansas State University, 2015)
Crop residue removal for livestock feeding and biofuel production at large scales must be evaluated to assess impacts on soil productivity and properties. Among all the potential negative impacts, wind erosion is a major concern in the central Great Plains. We conducted an on-farm study from 2011 to 2013 by removing crop residue at five levels (0, 25, 50, 75, and 100%) to determine the effects of crop residue removal on soil wind erosion parameters such as dry aggregate size distribution including soil wind erodible fraction (EF <0.84 mm aggregates), geometric mean diameter (GMD) and geometric standard deviation (GSD), dry aggregate stability, and soil surface roughness. The sub-model of Wind Erosion Prediction System (WEPS) developed by the USDA-ARS, Single-event Wind Erosion Evaluation Program (SWEEP) is a stand-alone companion software package that can be applied to simulate soil loss and dust emission from a single windstorm event. We applied measured data (i.e. EF, GMD, GSD, and roughness) to SWEEP for predicting wind velocity that can initiate wind erosion and soil loss under each crop residue removal condition with wind velocity at 13 m sˉ¹. The threshold wind velocity to initiate wind erosion generally decreased with increase in crop residue removal levels, particularly for residue removal >75%. The total amount of soil loss in 3 hours ranged from about 0.2 to 2.5 kg mˉ² and depends on soil condition and crop residue cover. On the other hand, high-yielding crops can produce abundant crop residue, which then raises the question that if a farmer wants to reduce residue, what could they do without removing it? The application of fertilizer on crop residue to stimulate microbial activity and subsequent decomposition of the residue is often debated. We conducted wheat straw decomposition field experiments under different fertilizer rates and combinations at three locations in western Kansas following wheat harvest in 2011 and 2012. A double shear box apparatus instrumented with a load cell measured the shear stress required to cut wheat straw and photomicrography was used to measure the cross-sectional area of wheat straw after shearing. Total C and N were also analyzed. The fertilizer rate and timing of application during summer 2012 and Fall 2013 at the Hays site had impacts on wheat straw shear stress at break point. Across site years, earlier (fall) fertilizer application generally resulted in lower remaining aboveground biomass as compared to a spring application. Multivariate and linear regressions suggested that N and C:N ratio partially explain the results observed with respect to treatment effects on winter wheat residue decomposition.
Keywords: Wind erosion; Crop residue removal; Crop residue decomposition; Shear strength; Agronomy (0285)